Assessment of the School Process Factors Affecting Plateau State Secondary Schools’ Effectiveness - Bako, M. M; Okereke, V. E.; Sara, S. S. (Kashere Journal of Education, 2021)
This study assessed the school process factors affecting Plateau state secondary schools’ effectiveness. Five research questions and five null hypotheses guided the study. Descriptive survey design was adopted for the study. A-43-items adapted questionnaire entitled School Process Effectiveness Factors Questionnaire” (SPEFQ) was used for data collection. The reliability of the instrument was determined through trial testing of 50 respondents and the data collected was tested using Cronbach Alpha statistics, which gave an overall reliability coefficient of 0.77. The population of the study comprised all the 2,599 teachers of public secondary schools across the three educational zones of Plateau state, out of which 519 respondents were sampled using proportionate stratified random sampling. The research questions were analyzed using mean scores. T-test and Kruskal Wallis One-way Analysis of Variance were used to test the null hypotheses at 0.05 level of significance. An overview of the results of the study showed that to a high extent, input, enabling conditions and teaching/learning process factors affect Plateau state secondary schools’ effectiveness. The findings further revealed that to a moderate extent, school climate factor affects Plateau state secondary schools’ effectiveness. Based on our findings, it was recommended that stakeholders in education should ensure that appropriate quality and quantity of input in terms of students’ enrolment, transition rate and clean school buildings and grounds are considered. In addition, capable teaching force be employed and subsequently promoted to man schools among others.